68Ga-PSMA PET/CT in patients with biochemical recurrence of prostate cancer: a prospective, 2-center study - Zacho, Helle Damgaard; Nielsen, Julie; Dettmann, Katja; Haberkorn, Uwe; Langkilde, Niels; Jensen, Jørgen; Petersen, Lars (Clinical nuclear medicine, 2018)
Purpose of the ReportThe aim of this study was to prospectively investigate the detection rate of 68Ga-PSMA PET/CT in biochemical recurrence (BCR) of prostate cancer and its impact on patient management.Materials and MethodsPatients with BCR after curatively intended treatment of prostate cancer wer
Im Titel ist die Zahl 68 hochgestellt
Gesehen am 10.03.2020